Ethical Issues of Social Media in Nigeria - Adams, Emmanuel Jibb; Dorcas, Baba (Indonesian Journal Publisher, 2024)
This study sought to analyse ethical concerns of social media in Nigeria. The theoretical framework adopted is the Source Credibility Theory. The study employed Critical Discourse Analysis. The population of the study consisted of the top four (4) social networking sites in Nigeria. Out of these, Twitter was purposively selected for its widespread use for youth activism, particularly within the context of the #EndSARS protest; and for being the only social media platform the federal government had temporarily banned for ethical violations. A convenient sample of ten (10) tweets, which included retweets with text and images posted both during and within 18 months after the protest, was used to collect secondary data. Findings demonstrated a mix of ethical and unethical use of Twitter within the context of the protest. The result also revealed that although Twitter is a credible source of information, there were instances of anonymous tweets, which cast some doubts on the credibility of that specific source. The study recommends that beyond social media regulations, there is a need for the promotion of media literacy in Nigeria’s workplaces and educational system. In addition, the form of self-regulation inherent in African ethics should be applied by users of social media to facilitate harmonious communication. This study has made a modest contribution in the area of source credibility theory by proposing a conceptual framework within the context of the study.